Chronic effects of flywheel training on physical capacities in soccer players: a systematic review - Allen, W. J.; De Keijzer, K. L.; Raya-González, J.; Castillo, D.; Coratella, G.; Beato, M. (Research in Sports Medicine, 2023)
The aims of the current systematic review were to evaluate the current literature surrounding the chronic effect of flywheel training on the physical capacities of soccer players, and to identify areas for future research to establish guidelines for its use.